Green Synthesis, Characterization and Antibacterial Activity of Zinc Oxide Nanoparticles using Leaf Extract of Rubia cordifolia - Prachi; Mushtaq, Asifa; Negi, Devendra Singh (Asian Journal of Chemistry, 2018)
This work reports the synthesis of zinc oxide nanoparticles using leaf extract of Rubia cordifolia, characterization and the antibacterial activities against selected pathogenic bacteria. X-ray diffraction showed that the particle are hexagonal wurtzite in nature and average crystallite size is 23.61 nm. The SEM image revealed that the particles are sheets in shape. TEM image indicates that the size is found in the range of 23.45 nm. Further, as-formed zinc oxide nanoparticles revealed significant antibacterial activity against gram negative Pseudomonas aeruginosa and Escherichia coli and Gram positive Micrococcus luteus, Staphylococcus aureus and Streptococcus pneumonia bacterial strain. The current investigation demonstrates convenient consumption of Rubia cordifolia leaf extract as a fuel for the synthesis of zinc oxide nanoparticles through green synthesis method to attain significantly antibacterial activity.